Our understanding of the role of exercise intensity can only be precise as our classification of exercise intensity - Gifford, J. R.; Larsen, J. (Experimental Physiology, 2023)
The physiological responses to exercise vary with exercise intensity. Traditionally, intensity of exercise has been classified relative to maximum rate of oxygen consumption (i.e., %VO2max) or maximum heart rate (i.e., %HRmax). This traditional mode of intensity classification does provide insight into general trends, but three often unacknowledged shortcomings prevent it from having the precision needed to accurately prescribe similar cardiometabolic conditions from one person to the next.